2014
DOI: 10.1172/jci74783
|View full text |Cite
|
Sign up to set email alerts
|

Resident fibroblast lineages mediate pressure overload–induced cardiac fibrosis

Abstract: Activation and accumulation of cardiac fibroblasts, which result in excessive extracellular matrix deposition and consequent mechanical stiffness, myocyte uncoupling, and ischemia, are key contributors to heart failure progression. Recently, endothelial-to-mesenchymal transition (EndoMT) and the recruitment of circulating hematopoietic progenitors to the heart have been reported to generate substantial numbers of cardiac fibroblasts in response to pressure overload-induced injury; therefore, these processes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
668
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 554 publications
(699 citation statements)
references
References 52 publications
28
668
1
2
Order By: Relevance
“…An early CRE-based lineage-tracing experiment suggested that a subset of cardiac stromal fibroblasts arise de novo via endothelial-tomesenchymal transition (EndMT) from adult endothelial cells (Zeisberg et al, 2007). However, more recent lineage-tracing studies have shown that the proliferation and expansion of resident fibroblasts during cardiac hypertrophy accounts for almost all cardiac fibroblasts (Ali et al, 2014;Moore-Morris et al, 2014). Around 80% of the fibroblasts had their origins in the epicardium, with the remainder derived from the endocardium via EndMT (Ali et al, 2014;Moore-Morris et al, 2014), although a limited number of adult fibroblasts in the right atrium and outflow tract region might derive from neural crest cells (Ali et al, 2014).…”
Section: Origins and Plasticity Of Cardiac Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…An early CRE-based lineage-tracing experiment suggested that a subset of cardiac stromal fibroblasts arise de novo via endothelial-tomesenchymal transition (EndMT) from adult endothelial cells (Zeisberg et al, 2007). However, more recent lineage-tracing studies have shown that the proliferation and expansion of resident fibroblasts during cardiac hypertrophy accounts for almost all cardiac fibroblasts (Ali et al, 2014;Moore-Morris et al, 2014). Around 80% of the fibroblasts had their origins in the epicardium, with the remainder derived from the endocardium via EndMT (Ali et al, 2014;Moore-Morris et al, 2014), although a limited number of adult fibroblasts in the right atrium and outflow tract region might derive from neural crest cells (Ali et al, 2014).…”
Section: Origins and Plasticity Of Cardiac Fibroblastsmentioning
confidence: 99%
“…However, more recent lineage-tracing studies have shown that the proliferation and expansion of resident fibroblasts during cardiac hypertrophy accounts for almost all cardiac fibroblasts (Ali et al, 2014;Moore-Morris et al, 2014). Around 80% of the fibroblasts had their origins in the epicardium, with the remainder derived from the endocardium via EndMT (Ali et al, 2014;Moore-Morris et al, 2014), although a limited number of adult fibroblasts in the right atrium and outflow tract region might derive from neural crest cells (Ali et al, 2014). Importantly, the developmental origin of adult stromal fibroblasts does not appear to affect the cellular fibroblast phenotype, transcriptional profile, response to apoptotic stimuli or proliferation rate (Ali et al, 2014).…”
Section: Origins and Plasticity Of Cardiac Fibroblastsmentioning
confidence: 99%
“…Here, we discuss limitations of these studies arising from markers utilized for cardiac fibroblasts, as well as our recently reported findings on cardiac fibroblast markers and origins 3 and their clinical impact.…”
Section: 2mentioning
confidence: 99%
“…1 However, our lineage tracing of adult endothelium with an inducible endothelial specific Cre, VEcadherin-CreERT2 did not reveal evidence that EndoMT had occurred. 3 A previous study performed to assess the occurrence of EndoMT utilized an endothelial Cre, Tie1-Cre, which labels both endothelial and haematopoietic lineages.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation